Academic Coaching in Higher Education: Mapping the Research Landscape through Bibliometric and Systematic Review - Muhammad Ainurrahman Wahid; Khaerudin Khaerudin; Uwes Anis Chaeruman; Imam Fitri Rahmadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
Academic coaching in higher education has grown rapidly, yet evidence remains fragmented. This study aims to map the global research landscape and synthesize key contributions. A mixed bibliometric–systematic review design was employed. First, a bibliometric analysis using Scopus (search date: 8 October 2025; keyword “academic coaching”) identified 2,154 documents. Second, a PRISMA-guided systematic review screened studies explicitly examining academic coaching in higher education, resulting in 31 articles for synthesis. Findings show sharp growth in publications after 2017, dominated by Anglophone countries particularly the United States and the United Kingdom with strong concentration in medical and health professions education. Thematic analysis highlights coaching as a reflective and relational learning strategy that fosters self-regulated learning, professional identity development, and psychosocial well-being. This review contributes novelty by integrating bibliometric mapping with systematic synthesis, offering a comprehensive framework for academic coaching research. Future studies should broaden contexts beyond Anglophone settings and employ longitudinal designs to strengthen evidence